Residential field site training project abstracts - 46th Batch Session: 2003-2004, 4th year MBBS students, CMC (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v19i2.3875Journal of Chittagong Medical College Teachers' Association 2008: 19(2):59-61